Studies on Aggregation and Adhesion of Platelets - Shively, J. A; Gott, C. L (Thrombosis and Haemostasis, 1967)
A modification of the Wright method for the evaluation of the aggregation and adhesive properties of platelets is described; the test is relatively simple and can be performed in a clinical laboratory.Using this procedure, the characteristics of platelets acidified to a pH of 6.5 from their normal pH by addition of small amounts of acid citrate dextrose (ACD) solution to platelet-rich plasma were evaluated. Aggregation and adhesive properties were decreased but returned to normal when the acidified platelets were resuspended in nonacidified platelet-poor plasma. These results confirm the transfusion and isotopie labeling survival studies using acidified platelets and indicate no significant injury of the platelets as exhibited by their aggregation and adhesive characteristics which are considered to be indicative of hemostatic function.